2019
DOI: 10.1371/journal.pone.0220150
|View full text |Cite
|
Sign up to set email alerts
|

Putting a stereotype to the test: The case of gender differences in multitasking costs in task-switching and dual-task situations

Abstract: According to a popular stereotype, women are better at multitasking than men, but empirical evidence for gender differences in multitasking performance is mixed. Previous work has focused on specific aspects of multitasking or has not considered gender differences in abilities contributing to multitasking performance. We therefore tested gender differences ( N = 96, 50% female) in sequential (i.e., task switching) and concurrent (i.e., dual tasking) multitasking, while controlling for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 38 publications
4
16
0
3
Order By: Relevance
“…The effect size with Cohen’s d = .5 is within the range of effect sizes (.27–.82 1 ) found in previous gender difference studies in multitasking (Hambrick et al, 2010; Mäntylä, 2013; Mäntylä et al, 2017; Stoet et al, 2013). It is also similar to the effect size used for power analysis in a similar recent study examining gender differences in both dual-task and task-switching paradigms was 0.6 (Hirsch et al, 2019). In addition, with the large number of tasks involved and measurement of personal computer usage, higher rates of attrition and of subject filtering (due to the failure to follow instructions) were expected.…”
Section: Methodssupporting
confidence: 74%
See 3 more Smart Citations
“…The effect size with Cohen’s d = .5 is within the range of effect sizes (.27–.82 1 ) found in previous gender difference studies in multitasking (Hambrick et al, 2010; Mäntylä, 2013; Mäntylä et al, 2017; Stoet et al, 2013). It is also similar to the effect size used for power analysis in a similar recent study examining gender differences in both dual-task and task-switching paradigms was 0.6 (Hirsch et al, 2019). In addition, with the large number of tasks involved and measurement of personal computer usage, higher rates of attrition and of subject filtering (due to the failure to follow instructions) were expected.…”
Section: Methodssupporting
confidence: 74%
“…It should be noted that the indicator where women’s advantage in task switching was found was mixing cost but not switch cost in Stoet et al (2013). In addition, the sample size of this study ( N = 117), while larger than that of Hirsch et al (2019) which found no gender difference in either dual-task or task-switching performance ( N = 96), was smaller than that of Stoet et al (2013) ( N = 231). One may question whether the non-significant result was simply due to a smaller sample size of this study.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…These results are also in line with findings from previous studies in which females appear to demonstrate higher multitasking and emotion regulation needs, and to manage their emotions more poorly than males and present with higher problematic smartphone use ( 146 , 152 , 263 266 ). Evidence regarding gender differences in multitasking is inconclusive due to conflicting findings, with some evidence suggesting that women are not better than men at multitasking, while other literature suggests that women present with better multitasking skills ( 151 , 267 ). To explain these differences, the hunter-gatherer hypothesis (claiming a cognitive adaptation to different division of labor roles across the sexes) ( 268 ) has been proposed to explain findings of females being less affected by task-irrelevant interruptions in experimentally-generated multitasking conditions, suggesting that females are better at multitasking.…”
Section: Discussionmentioning
confidence: 99%